Tawaran: Layanan Konseling Berbasis Meditasi dalam Mengurangi Stres pada Generasi Millenial (Jurnal Bimbingan dan Konseling Islam, 2019)
The purpose of this article is to try to make a counseling service offering by using breathing meditation that includes spells to reduce the stress currently experienced by the millennial generation. This article uses research in the form of literature review, by gathering a number of references related to meditation and stress, both in the form of journals and reference books. Stress is the gap between environmental demands and the ability of individuals to fulfill both physically and spiritually which results in the stressful stress that is currently mostly experienced by millennials. The result of this article is to make an offer in the form of counseling based on breathing meditation by using mantras in the form of prayer, by utilizing rhythmic breathing to guide a person into deep meditation or a relaxed mental state. Meditation that is done regularly can reduce stress.